El bien de los cónyuges y nulidad matrimonial - Torres Escudero, Bernardo (Revista española de derecho canónico, 2024)
Currently there is unanimity in doctrine and jurisprudence in considering that the good of the spouses is an essential element of the lifelong consortium, and therefore the object of matrimonial consent. In the case of the exclusion of the property of the spouses, it is obvious that it is not easy to determine, in each specific case, when one or both spouses have made its exclusion, at the time of the provision of the matrimonial consent. This article is an approach to the problem.